Modification of the Battle to Improve Learning Outcomes in The Game of Rasel Ball Students of Grade IV of SDN 3 Balaesang Tanjung - Iswanto, Iswanto; Rahmah, Rahmah; Rifandy, Arief Aditya; Liloi, Delvi Kristanti (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The purpose of this study is to improve the learning outcomes of baseball games through modified bats for fourth-grade students of SDN 3 Balaesang Tanjung. This study is a classroom action research (CAR), which is one type of research conducted by teachers to improve the quality of learning in the classroom. This study took place at SDN 3 Balaesang Tanjung, Balaesang Tanjung District, Donggala Regency, Central Sulawesi Province and used school yard facilities for the implementation of baseball hitting skills learning using modified baseball bats. Elementary school students of SDN 3 Balaesang Tanjung. The class to be studied is class IV which consists of 17 male students and 11 female students. The total number of research subjects is 28 students. Based on the results of the study regarding classroom action research with the title